Analisis Faktor Tingkat Kepuasan Pelanggan Bus Patas Sugeng Rahayu Dengan Menggunakan Metode Customer Satisfication Index (CSI) - Fithri Estikhamah; Nugroho Utomo (KERN, 2019)
In a situation of business competition is more advanced as it is today, bus company (PO) required to gets more creative and innovative in looking for or retain customers. As PO Sumber Group that has opened the route “PATAS” to track JOGYA / SEMARANG - SOLO - SURABAYA via Karangjati in early 2015 and by the name of SUGENG RAHAYU by GOLDEN STAR. Under SUMBER GROUP and under management Golden Star. Based on these problems purpose of this research is to determine what percentage of the level of customer satisfaction on the performance Sugeng Rahayu “Patas” bus. Due to the limited sample does not then take a sample of 100 respondents. Techniques of collecting data using questionnaires. Analysis techniques used is to use the Customer Satisfaction Index (CSI). It is based on five dimensions of service quality are tangibles (physical evidence), reliability, responsiveness, assurance, and empathy. The results showed that overall customer satisfaction has a value of 78.5%, this means that customers are satisfied with the services provided by Sugeng Rahayu ”Patas” bus. Although the results of the analysis show a good value but there needs to be improvement of service quality, especially the cleanliness of toilets in the bus.